Immunogenicity and safety of MF59-adjuvanted quadrivalent influenza vaccine versus standard and alternate B strain MF59-adjuvanted trivalent influenza vaccines in older adults. Issue 2 (10th January 2020) - Essink, Brandon; Fierro, Carlos; Rosen, Jeffrey; Figueroa, Amparo L.; Zhang, Bin; Verhoeven, Carole; Edelman, Jonathan; Smolenov, Igor
Highlights: aQIV-associated GMTs and seroconversion rates are noninferior to those of aTIV. aQIV immunogenicity is superior for B strains not included in aTIV. aQIV was well tolerated in adults aged ≥65 years. aQIV is suitable for vaccination of adults aged ≥65 years. Abstract: Objective: Evaluate whether adjuvanted quadrivalent influenza vaccine (aQIV) elicits a noninferior immune response compared with a licensed adjuvanted trivalent influenza vaccine (aTIV-1; Fluad™) and aTIV-2 containing an alternate B strain, examine whether aQIV had immunological superiority for the B strain absent from aTIV comparators, and evaluate reactogenicity and safety among adults ≥65 years. Methods: In a multicenter, double-blind, randomized controlled trial, adults ≥65 years were randomized 2:1:1 to vaccination with aQIV (n = 889), aTIV-1 (n = 445), or aTIV-2 (n = 444) during the 2017-2018 influenza season. Immunogenicity was assessed by hemagglutination inhibition (HI) assay conducted on serum samples collected before vaccination and 21 days after vaccination for homologous influenza strains. Results: aQIV met non-inferiority criteria for geometric mean titer ratios (GMT ratios) and seroconversion rate (SCR) differences against aTIV. The upper bounds of the 2-sided 95% confidence interval (CI) for GMT ratios were <1.5 for all 4 strains (A/H1N1 = 1.27, A/H3N2 = 1.09, B-Yamagata = 1.08, B-Victoria = 1.08). The upper bounds of the 95% CI of the SCR differences were <10% for all 4 strains (A/H1N1 = 7.76%, A/H3N2 = 4.96%, B-Yamagata = 3.27%, B-Victoria = 2.55%). aQIV also met superiority criteria (upper bound of 95% CI for GMT ratios <1 and SCR differences <0) for B strain absent from aTIV comparators (B-Yamagata GMT ratio = 0.70, SCR difference = −8.81%; B-Victoria GMT ratio = 0.78, SCR difference = −8.11%). aQIV and aTIV vaccines were immunogenic and well-tolerated. The immunological benefit of aQIV was also demonstrated in age subgroups 65–74 years, 75–84 years, and ≥85 years and in those with high comorbidity risk scores. Reactogenicity profiles were generally comparable. Conclusion: aQIV induces a similar immune response as the licensed aTIV vaccine against homologous influenza strains and has a comparable reactogenicity and safety profile. Superior immunogenicity against the additional B strain was observed, indicating that aQIV could provide a broader protection than aTIV against influenza in older adults (NCT03314662).